Some endemic fishing methods in the Philippines. - Guerrero, Marcial S. (Miagao, Iloilo College of Fisheries, University of the Philippines, 1954)
In the Philippines, it is known that our forefathers were of Malay origin that came to our country to seek better ways of living wealth and spiritual well being. This migratory people brought with them some methods of capturing fish, using panilo, fish shelter, fish trap, scoop net and many others. Later, the Japanese came and introduced the so-called beam trawl, used in the latter part of the twentieth century, towed by powered vessels. After this, the Filipinos were awakened and began make their own fishing methods and modify introduces ones. Soon, their hard earned toils were repaid. They made the perfected mestizo otter trawl, motorized basnigan outfit, motorized push nets and many other well-developed form of fishing paraphernalia, which we have now in use by our subsistence and commercial fishermen. Our government, seeing the needs of the common tao, launched an economic development program. In this program, the Philippine institute of fisheries technology and the bureau of fisheries have been training the policies for conservation and management of our fisheries. The institute of trains the students on how's, the why's, and what's of fishing industry and the bureau sees to it that the fishing industry attain its maximum productivity through legal ways. These reports pursued during my apprenticeship have been submitted to contribute in one way or another to the objectives of the Philippine institute of fisheries technology in its efforts to modernize the incorporated herein public as well as m future fishery students information. It is hoped the in these reports, others may find enjoyment and fruitful fisheries knowledge.
Keywords: Fish-Capture.